(untitled) (Journal of the College of Basic Education, 2022)
Educators in various parts of the world emphasized the importance of developing the students’ mental processes and taking into account their tendencies, and thus their motor and social skills may increase. others with the aim of building his scientific trends, developing his talents, and preparing him comprehensively.